lnstitutionalising community based monitoring and evaluation process: experiences from Nigeria. (2010)
Over the years, Community Development seems to have treated social relations and responsibilities using Top-Bottom approach. Due to the problems associated with the approach over time, a refined participatory approach emerged to bye-pass problems such as project abandonment, corruption, alienation and non sustainability of projects under the Top-Bottom Policy and Practice. In this new approach of Community Driven Development (CCD), stakeholders, especially at the grassroots, are called upon to take their destiny in their own hands beginning from needs assessment to that of project implementation, launching, utilization and sustenance of project. In addition, its Community Empowerment orientation has a built-in internally driven and Community Based Monitoring and Evaluation. This is to ensure full-scale empowerment and total ownership of the Development process by the grassroots. Following this approach several questions emerge. Specifically, how feasible is the Community Based Monitoring and Evaluation (CBM&E) process under the ongoing Community based poverty Reduction Projects in Nigeria within the backdrop of the failed top-bottom practice which developed the attitude of apathy to development projects amongst the grassroots especially in Nigeria? Drawing from the pilot experiences in some communities currently drawing from the social fund of the World Bank under the CBPRP in Nigeria, this paper sees hope in the process and suggests a greater investment in it. This is not only based on the empowerment process in itself, but also that, in the process; is the capability to banish the culture of silence and its ability to engender higher involvement and ultimate sustainability of projects especially by the poorest of the poor.